The Need for Early Prevention of Offenses Among Students of Higher Educational Institutions - Anvarovna, Dadaboeva Jumagul (Indonesian Journal of Public Administration Review, 2025)
Today, youth crime is among the most acute social problems of our society. Practice shows that the state, as a rule, spends its main forces and resources on combating crime itself, although it has long been necessary to create a well-coordinated and fundamentally new prevention system that should be aimed at eliminating the causes and conditions that give rise to crime and preventive prevention. The main aim of article is prevention of offenses among students is a multifaceted, interdisciplinary and interdepartmental task. The efforts of many government agencies, public associations, foundations, and institutions designed to address the causes and conditions that contribute to the spread of offenses among adolescents and youth are focused on its solution. So, in this article highlights of the need for early prevention of offenses among students of higher educational institutions in our conditionToday, youth crime is among the most acute social problems of our society. Practice shows that the state, as a rule, spends its main forces and resources on combating crime itself, although it has long been necessary to create a well-coordinated and fundamentally new prevention system that should be aimed at eliminating the causes and conditions that give rise to crime and preventive prevention. The main aim of article is prevention of offenses among students is a multifaceted, interdisciplinary and interdepartmental task. The efforts of many government agencies, public associations, foundations, and institutions designed to address the causes and conditions that contribute to the spread of offenses among adolescents and youth are focused on its solution. So, in this article highlights of the need for early prevention of offenses among students of higher educational institutions in our condition